2000
DOI: 10.1002/1096-8628(20000904)94:1<32::aid-ajmg7>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Congenital absence of lacrimal puncta and salivary glands: Report of a Brazilian family and review

Abstract: Congenital absence of the salivary glands and lacrimal puncta is a rare autosomal-dominant disorder with variable expressivity. Only a few instances of this condition have been reported. We present the first Brazilian observation of this syndrome and a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 10 publications
0
19
0
1
Order By: Relevance
“…2 Other complications include periodontal disease, oral soft tissue inflammation and disorders of smell, chewing and swallowing. 3 We previously identified loss of function mutations in the fibroblast growth factor 10 (FGF10) gene associated with ALSG. 1 More recent studies have shown ALSG to be allelic to lacrimo-auriculo-dento-digital (LADD; OMIM 149730) syndrome, which is a similar clinical entity.…”
Section: Introductionmentioning
confidence: 99%
“…2 Other complications include periodontal disease, oral soft tissue inflammation and disorders of smell, chewing and swallowing. 3 We previously identified loss of function mutations in the fibroblast growth factor 10 (FGF10) gene associated with ALSG. 1 More recent studies have shown ALSG to be allelic to lacrimo-auriculo-dento-digital (LADD; OMIM 149730) syndrome, which is a similar clinical entity.…”
Section: Introductionmentioning
confidence: 99%
“…However, in 75% of the reported cases, the aplasia occurred on the righthand side, as in our case. Salivary gland aplasia is frequently associated with other congenital defects, such as lacrimal gland agenesis, absence of lacrimal puncta, [4] 1894 Right (2) Abdel-Dayem [16] 1978 Left (3) Kubo et al [6] 1990 Right (4) Garcia-Consuegra et al [7] 1999 Left (5) Yılmaz et al [4] 2002 Right (6) Roh [8] 2006 Right (7) Srinivasan et al [5] 2006 Right (8) Suzuki et al [13] 2007 Right (9) Shipchandler and Lorenz [12] 2008 Left (10) Koo et al [9] 2009 Left (case 1) Right (case 1) (12) Gupta et al [11] 2009 Right (13) Yanir et al [14] 2009 Right (14) Yılmaz et al [15] 2009 Right (15) Gallego et al [10] 2009 Right ( orbital abnormalities, ectodermal dysplasia, and cleft lip and palate [1,[17][18][19][20][21]. Less frequently, it appears as an isolated phenomenon [2][3][4][5][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral aplasia of submandibular gland is an extremely rare disorder; only 15 cases have been reported in the medical literature to date [4][5][6][7][8][9][10][11][12][13][14][15][16]. Salivary gland aplasia may ocur in isolation or it may be associated with other ectodermal defects [1,[17][18][19][20][21]. Patients may be asymptomatic [4,5,14,22,23] or may suffer xerostomia, dysphagia, taste alterations, oral burning, or extensive dental caries [1,2,10,15,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The opening on the lower eyelid border is more visible than the opening on the upper eyelid border. Absence of the lacrimal punctum is uncommon [Ferreira et al, 2000] and although it is typically presumed to be caused by agenesis, we avoid causal mechanisms in this terminology. There was some disagreement as to whether Nasolacrimal duct obstruction should be included in this terminology.…”
Section: Lacrimal Punctum Absencementioning
confidence: 99%